Effects of footwear sample area on the friction coefficient on the floor - Hung-Kai Tsai; Kai-Way Li; Ching-Chung Chen (2015 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2015)
Slips & falls are common. The coefficient of friction (COF) at footwear and floor interface is one of the major term to determine the risk of slip & fall. Past research has been focused on surface contamination, footwear tread, and floor roughness, the footwear sample area has rarely been discussed. This research was designed to investigate the effects of footwear sample area on the COF on the floor. Five footwear sample areas were tested on two floors and three floor surfaces conditions. A Brungrber Mark II slipmeter was used. The results showed that footwear sample area, floor, and surface condition were all significant (p<;0.05) factors affects the COF. On liquid contaminated conditions, the larger the footwear sample was, the lower the COF of the floor was. This was consistent with the squeeze film equation by Moore [11].